On (L, M)-Double Fuzzy Filter Spaces. (15th May 2018) - Abd El-Latif, A. A.; Aygün, H.; Çetkin, V.
Abstract : We give in this paper the definitions of ( L, M ) -double fuzzy filter base and ( L, M ) -double fuzzy filter structures where L and M are strictly two-sided commutative quantales, and we also investigate the relations between them. Moreover, we propose second-order image and preimage operators of ( L, M ) -double fuzzy filter base and study some of its fundamental properties. Finally, we handle the given structures in the categorical aspect. For instance, we show that the category ( L, M ) -DFIL of ( L, M ) -double fuzzy filter spaces and filter maps between these spaces is a topological category over the category SET .